Linux System Programming Techniques : Become a Proficient Linux System Programmer Using Expert Recipes and Techniques. - Persson, Jack-Benny (Packt Publishing, Limited, 2021)
Find solutions to all your problems related to Linux system programming using practical recipes for developing your own system programs Key Features Develop a deeper understanding of how Linux system programming works Gain hands-on experience of working with different Linux projects with the help of practical examples Learn how to develop your own programs for Linux Book DescriptionLinux is the world's most popular open source operating system (OS). Linux System Programming Techniques will enable you to extend the Linux OS with your own system programs and communicate with other programs on the system. The book begins by exploring the Linux filesystem, its basic commands, built-in manual pages, the GNU compiler collection (GCC), and Linux system calls. You'll then discover how to handle errors in your programs and will learn to catch errors and print relevant information about them. The book takes you through multiple recipes on how to read and write files on the system, using both streams and file descriptors. As you advance, you'll delve into forking, creating zombie processes, and daemons, along with recipes on how to handle daemons using systemd. After this, you'll find out how to create shared libraries and start exploring different types of interprocess communication (IPC). In the later chapters, recipes on how to write programs using POSIX threads and how to debug your programs using the GNU debugger (GDB) and Valgrind will also be covered. By the end of this Linux book, you will be able to develop your own system programs for Linux, including daemons, tools, clients, and filters. What you will learn Discover how to write programs for the Linux system using a wide variety of system calls Delve into the working of POSIX functions Understand and use key concepts such as signals, pipes, IPC, and process management Find out how to integrate programs with a Linux system Explore advanced topics such as filesystem operations, creating shared libraries, and debugging your programs Gain an overall understanding of how to debug your programs using Valgrind Who this book is for This book is for anyone who wants to develop system programs for Linux and gain a deeper understanding of the Linux system. The book is beneficial for anyone who is facing issues related to a particular part of Linux system programming and is looking for specific recipes or solutions.